Análisis de las políticas y procedimientos del control interno y su incidencia en la calidad de información financiera de la empresa campo fino del cantón salcedo en el año 2018 - Calvopiña Toapanta, Gloria Beatriz (2019)
This research was carried out at "Campo Fino" company considering that, it does not have a well-structured and social internal control manual, which is why inconsistencies have been presented at the different levels of the organization. Analyzing the internal control policies and procedures and their impact on the financial information quality was the objective of this research. Descriptive research on the operations of the financial department was the methodology used in order to determine the vulnerabilities in terms of internal control; In addition, a bibliographic research was carried out too, theoretically support the subject under study and analyze possible solutions to similar problems and a field investigation, to know the current situation of the company, for this surveys and interviews were carried out to those responsible for the financial area of the organization. The main results obtained are summarized in that, the company performs several internal control activities. However, they do so empirically, that is, they do not perform the required technical processes that minimize the occurrence of inconsistencies such as wasting resources and lack of controls, among others, that limit business development and competitiveness, leading to the conclusion that none of these affects financial information because the financial area, being a strategic area, maintains undocumented but rigorous procedures the error and fraud is reduced, since this in turn have adopted norms, policies and procedures that govern in a way that is controlled.